Composite ceramic diaphragm with temperature resistance and liquid retention as well as preparation method and application of composite ceramic diaphragm
By introducing crosslinkable polymer adhesive and modified coating into the ceramic diaphragm, the temperature resistance and liquid retention of the ceramic diaphragm are improved by using boron-containing reinforcement and hydroxyl-containing polymers, and the problem of poor mechanical strength and temperature resistance of the ceramic diaphragm under high temperature conditions is solved.
Patent Information
- Application Number
- CN202411769842.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing ceramic diaphragms have poor mechanical strength and temperature resistance under high temperature conditions, and also have poor liquid retention.
A crosslinkable polymer binder is introduced into the coating of the ceramic separator, and a modified coating is formed on the surface, which consists of a boron-containing reinforcement and a hydroxyl-containing polymer, which enhances the crosslinking degree and electrolyte properties through the impregnation liquid.
The mechanical strength, temperature resistance and liquid retention of the ceramic diaphragm are improved, ensuring a lower heat shrinkage rate and a higher liquid absorbance and liquid retention volume under high temperature conditions.
Smart Images

Figure BDA0005169982100000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic diaphragms, and in particular to a composite ceramic diaphragm having both temperature resistance and liquid retention properties, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become a hot topic in power technology research in recent years due to their advantages of high specific energy, long cycle life, no memory effect (compared to nickel-chromium batteries), and safety, reliability, and ability to withstand rapid re-discharge. Lithium-ion batteries play an irreplaceable role in widely used electronic devices such as mobile phones, laptops, etc., as well as the emerging electric and hybrid electric vehicles.
[0003] The main structure of lithium-ion batteries includes positive / negative electrode materials, electrolytes, battery separators and battery shell outer packaging materials. Battery separators are an important component of lithium-ion batteries. They play a role in directly separating positive and negative electrodes and preventing battery short circuits. The performance of battery separators directly determines the interface performance, cycle performance and safety performance of batteries. Therefore, excellent separators play a vital role in improving the overall performance of batteries.
[0004] Ceramics are widely used in the coating of diaphragms because they can be dispersed in water and are environmentally friendly, so as to prepare high-temperature resistant ceramic coating diaphragms with good thermal stability. The wettability of electrolyte is an important indicator for evaluating diaphragms. Excellent electrolyte wettability is beneficial to improving the ionic conductivity of the battery. In order to further improve the ability of lithium battery diaphragms to absorb electrolytes, a polymer adhesive containing polar hydrophilic groups is usually introduced into the diaphragm coating. For example, the patent technical document CN108305972B discloses a ceramic coating diaphragm and a preparation method and application thereof. The ceramic coating diaphragm includes a base film and a ceramic coating, wherein the ceramic coating is coated with inorganic particles with polyethylene glycol grafted on the surface, and the inorganic particles are grafted with polyethylene glycol having a hydroxyl group. Although the ceramic coating diaphragm has a fast liquid absorption rate and a high liquid absorption rate, it exhibits a large thermal shrinkage under high temperature conditions, resulting in poor mechanical strength and temperature resistance of the ceramic coating diaphragm at high temperatures.
[0005] In order to solve the above problems, a cross-linkable polymer adhesive can be introduced into the diaphragm coating to form a three-dimensional network structure on the diaphragm surface to increase the mechanical strength and temperature resistance of the ceramic coating diaphragm. For example, patent document CN113964450A discloses a battery diaphragm coating liquid and a preparation method thereof, a battery diaphragm and a battery. In the battery diaphragm coating liquid, due to the interaction force or hydrogen bond between ceramics, adhesives, nanowires and coupling agents, a structure of ... ceramic-coupling agent-nanowire-ceramic-coupling agent-nanowire... is formed, so that the final battery diaphragm has good heat resistance. However, the ceramic diaphragm prepared by this method has a high degree of cross-linking, so that the internal stacking of the system is relatively dense, resulting in poor liquid retention of the final ceramic diaphragm. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose a composite ceramic diaphragm that takes into account both temperature resistance and liquid retention, and a preparation method and application thereof, so as to solve the problems of poor temperature resistance and poor liquid retention of ceramic diaphragms in the prior art.
[0007] Based on the above purpose, the present invention provides a composite ceramic diaphragm that takes into account both temperature resistance and liquid retention, the diaphragm comprising a ceramic coated diaphragm and a modified coating coated on at least one surface thereof;
[0008] The modified coating is obtained by coating the coating slurry on the surface of the ceramic coating diaphragm, drying it and then soaking it in an impregnation liquid;
[0009] The mass ratio of the coating slurry to the impregnating material is 100:10-20;
[0010] The coating slurry comprises the following raw materials by weight: 0.1-0.3 parts of alkaline metal compound, 3-5 parts of binder, 40-80 parts of hydroxyl-containing polymer, 20-50 parts of boron-containing reinforcing agent, 0.5-1.5 parts of auxiliary agent, and 80-100 parts of deionized water;
[0011] The hydroxyl-containing polymer is any one of nano bamboo charcoal powder, polyvinyl alcohol and polyethylene glycol;
[0012] The boron-containing reinforcing agent is a carbon nanotube coated with boric acid;
[0013] The impregnating material is an aqueous solution containing borate ions.
[0014] Preferably, the preparation method of the boron-containing enhancer is as follows:
[0015] S11. The carbon nanotubes were added to concentrated sulfuric acid, stirred for 10-12 hours, sodium nitrate and potassium permanganate were added, and heated in an oil bath at 38-42°C for 25-32 minutes, and then deionized water and a 30% by mass fraction of hydrogen peroxide aqueous solution were added, stirred for 20-30 minutes, and then washed and freeze-dried to obtain modified carbon nanotubes;
[0016] S12. Ultrasonic disperse the modified carbon nanotubes in deionized water for 1.5-2h, add an anhydrous ethanol solution of boric acid, add the dispersed modified carbon nanotube aqueous solution dropwise into the anhydrous ethanol solution of boric acid, stir in a water bath at 60-65°C until dry, and then dry at 65-70°C for 4-5h to obtain a boron-containing enhancer.
[0017] Preferably, in step S1, the usage ratio of the carbon nanotubes, concentrated sulfuric acid, sodium nitrate, potassium permanganate, deionized water and 30% aqueous hydrogen peroxide solution is 8-12 g: 20-25 mL: 0.3-0.4 g: 0.8-1.2 g: 35-40 mL: 8-12 mL.
[0018] Preferably, in step S2, the mass ratio of the modified carbon nanotubes, deionized water and anhydrous ethanol solution of boric acid is 3-7:18-22:50-60, and the mass fraction of the anhydrous ethanol solution of boric acid is 8%-12%.
[0019] Preferably, the alkaline metal compound is any one of nano-aluminum oxide, aluminum hydroxide and magnesium hydroxide.
[0020] Preferably, the binder is any one of styrene-butadiene rubber, polyvinyl alcohol and polyvinylidene fluoride.
[0021] Preferably, the auxiliary agent is any one of succinic acid, fluoroalkyl methoxy ether alcohol, sodium polyacrylate, acetylene glycol vinyl ether, fatty acid polyoxyethylene ether and polyether-modified siloxane.
[0022] Preferably, the concentration of the aqueous solution containing borate ions is 3%-7%;
[0023] The aqueous solution containing borate ions is obtained by dissolving a boron-containing inorganic compound in water;
[0024] The boron-containing inorganic compound is any one of borax, potassium tetraborate, lithium tetraborate and ammonium borate.
[0025] Preferably, the coating method is any one of micro-gravure coating, dip coating, blade coating, spray coating and spot coating.
[0026] Furthermore, the present invention also provides a method for preparing a composite ceramic diaphragm having both heat resistance and liquid retention, comprising the following steps:
[0027] S21. The binder, the hydroxyl-containing polymer and deionized water were mixed and stirred for 30-60 min to obtain a mixture A;
[0028] S22. Add the alkaline metal compound, the boron-containing enhancer and the additive to the mixture A and stir for 30-60 min to obtain a mixture B;
[0029] S23. The mixture B was passed through a magnetic filtration device, stirred for 5-20 min, and then filtered through a 250-mesh filter to obtain a coating slurry;
[0030] S24. The coating slurry is applied to one or both sides of the polyolefin base film, and a composite film is obtained after drying;
[0031] S25. Immerse the composite membrane in the impregnating material for 10-20 minutes, and after drying, obtain a composite ceramic diaphragm having both heat resistance and liquid retention.
[0032] Furthermore, the present invention also provides an application of a composite ceramic diaphragm that has both heat resistance and liquid retention, which can be used in lithium-ion batteries.
[0033] Beneficial effects of the present invention:
[0034] The boron-containing reinforcing agent provided by the present invention is a boric acid-coated carbon nanotube, which is compounded with a hydroxyl-containing polymer to increase the liquid retention capacity of the ceramic diaphragm for the electrolyte and effectively improve the liquid absorption rate and temperature resistance of the ceramic diaphragm.
[0035] The impregnation liquid provided by the present invention is an aqueous solution containing borate ions. After immersing the composite membrane prepared by the boron-containing enhancer, the cross-linking degree inside the system and the affinity of the system to the electrolyte can be further enhanced, thereby further increasing the temperature resistance of the ceramic diaphragm while further improving the liquid absorption and liquid retention of the ceramic diaphragm.
[0036] The ceramic diaphragm prepared by the present invention has high temperature resistance, low heat shrinkage at high temperature, and high liquid absorption and liquid retention, so it has broad application prospects. DETAILED DESCRIPTION
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0038] Embodiment 1: A method for preparing a composite ceramic diaphragm having both heat resistance and liquid retention, comprising the following steps:
[0039] S1. 8 g of carbon nanotubes were added to 20 g of concentrated sulfuric acid, stirred for 10 h, 0.3 g of sodium nitrate and 0.8 g of potassium permanganate were added, and the mixture was heated in an oil bath at 38 ° C for 25 min, and then 35 g of deionized water and 8 g of a 30% aqueous hydrogen peroxide solution were added, stirred for 20 min, and then washed and freeze-dried to obtain modified carbon nanotubes;
[0040] S2. 3 g of modified carbon nanotubes were ultrasonically dispersed in 18 g of deionized water for 1.5 h, and the dispersed modified carbon nanotube aqueous solution was dropwise added to 50 g of an 8% by mass boric acid anhydrous ethanol solution, stirred in a 60 ° C water bath until dry, and then dried at 65 ° C for 4 h to obtain a boron-containing enhancer;
[0041] S3. 3g of styrene-butadiene rubber, 40g of nano bamboo charcoal powder and 80g of deionized water were mixed and stirred for 30min to obtain a mixture A;
[0042] S4. 0.1 g of nano-alumina, 20 g of boron-containing enhancer and 0.5 g of succinic acid were added to 123 g of mixture A and stirred for 30 min to obtain a mixture B;
[0043] S5. The mixture B was passed through a magnetic filtration device, stirred for 5 min, and then filtered through a 250-mesh filter to obtain a coating slurry;
[0044] S6. The coating slurry is applied to both sides of the polyolefin base film and dried to obtain a composite film;
[0045] S7. Dissolve 30 g of borax in 1000 g of water to obtain an impregnated material;
[0046] S8. The composite membrane is immersed in 10 g of the impregnating material for 10 minutes, and after drying, a composite ceramic diaphragm having both heat resistance and liquid retention is obtained.
[0047] Embodiment 2: A method for preparing a composite ceramic diaphragm having both heat resistance and liquid retention, comprising the following steps:
[0048] S1. 9 g of carbon nanotubes were added to 22 g of concentrated sulfuric acid, stirred for 11 h, 0.33 g of sodium nitrate and 1 g of potassium permanganate were added, and the mixture was heated in an oil bath at 40 ° C for 28 min, and then 36 g of deionized water and 10 g of a 30% aqueous hydrogen peroxide solution were added, stirred for 23 min, and then washed and freeze-dried to obtain modified carbon nanotubes;
[0049] S2. 5 g of modified carbon nanotubes were ultrasonically dispersed in 19 g of deionized water for 1.7 h, and the dispersed modified carbon nanotube aqueous solution was dropwise added to 53 g of anhydrous ethanol solution of 9% boric acid by mass, stirred in a water bath at 62 ° C until dry, and then dried at 67 ° C for 4.3 h to obtain a boron-containing enhancer;
[0050] S3. 3.7 g of polyvinyl alcohol, 60 g of polyvinyl alcohol and 87 g of deionized water were mixed and stirred for 40 min to obtain a mixture A;
[0051] S4. To 150 g of mixture A was added 0.2 g of aluminum hydroxide, 30 g of a boron-containing enhancer and 0.8 g of a fluoroalkyl methoxy ether alcohol and stirred for 40 min to obtain a mixture B;
[0052] S5. The mixture B was passed through a magnetic filtration device, stirred for 10 min, and then filtered through a 250-mesh filter to obtain a coating slurry;
[0053] S6. The coating slurry is applied to both sides of the polyolefin base film and dried to obtain a composite film;
[0054] S7. Dissolve 40 g of potassium tetraborate in 1000 g of water to obtain an impregnated material;
[0055] S8. The composite membrane is immersed in 13 g of impregnating material for 17 minutes, and after drying, a composite ceramic diaphragm having both heat resistance and liquid retention is obtained.
[0056] Embodiment 3: A method for preparing a composite ceramic diaphragm having both heat resistance and liquid retention, comprising the following steps:
[0057] S1. 10 g of carbon nanotubes were added to 24 g of concentrated sulfuric acid, stirred for 11 h, 0.36 g of sodium nitrate and 1.1 g of potassium permanganate were added, and the mixture was heated in an oil bath at 41 ° C for 30 min, and then 38 g of deionized water and 11 g of a 30% aqueous hydrogen peroxide solution were added, stirred for 26 min, and then washed and freeze-dried to obtain modified carbon nanotubes;
[0058] S2. 6 g of modified carbon nanotubes were ultrasonically dispersed in 20 g of deionized water for 1.9 h, and the dispersed modified carbon nanotube aqueous solution was dropwise added to 56 g of anhydrous ethanol solution of 11% boric acid by mass, stirred in a water bath at 64 ° C until dry, and then dried at 69 ° C for 4.6 h to obtain a boron-containing enhancer;
[0059] S3. 4.3 g of polyvinylidene fluoride, 70 g of polyethylene glycol and 94 g of deionized water were mixed and stirred for 50 min to obtain a mixture A;
[0060] S4. To 170 g of mixture A was added 0.2 g of magnesium hydroxide, 40 g of a boron-containing enhancer and 1.2 g of sodium polyacrylate and stirred for 50 min to obtain a mixture B;
[0061] S5. The mixture B was passed through a magnetic filtration device, stirred for 15 min, and then filtered through a 250-mesh filter to obtain a coating slurry;
[0062] S6. The coating slurry is applied to both sides of the polyolefin base film and dried to obtain a composite film;
[0063] S7. Dissolve 50 g of lithium tetraborate in 1000 g of water to obtain an impregnated material;
[0064] S8. The composite membrane is immersed in 16 g of the impregnating material for 18 minutes, and after drying, a composite ceramic diaphragm having both heat resistance and liquid retention is obtained.
[0065] Embodiment 4: A method for preparing a composite ceramic diaphragm having both heat resistance and liquid retention, comprising the following steps:
[0066] S1. 12 g of carbon nanotubes were added to 25 g of concentrated sulfuric acid, stirred for 12 h, 0.4 g of sodium nitrate and 1.2 g of potassium permanganate were added, and the mixture was heated in an oil bath at 42 ° C for 32 min, and then 40 g of deionized water and 12 g of a 30% aqueous hydrogen peroxide solution were added, stirred for 30 min, and then washed and freeze-dried to obtain modified carbon nanotubes;
[0067] S2. 7 g of modified carbon nanotubes were ultrasonically dispersed in 22 g of deionized water for 2 h, and the dispersed modified carbon nanotube aqueous solution was dropwise added to 60 g of anhydrous ethanol solution of 12% by mass of boric acid, stirred in a water bath at 65 ° C until dry, and then dried at 70 ° C for 5 h to obtain a boron-containing enhancer;
[0068] S3. 5 g of polyvinylidene fluoride, 80 g of polyethylene glycol and 100 g of deionized water were mixed and stirred for 60 min to obtain a mixture A;
[0069] S4. To 185 g of mixture A was added 0.3 g of magnesium hydroxide, 50 g of a boron-containing enhancer and 1.5 g of acetylene glycol vinyl ether and stirred for 60 min to obtain a mixture B;
[0070] S5. The mixture B was passed through a magnetic filtration device, stirred for 20 min, and then filtered through a 250-mesh filter to obtain a coating slurry;
[0071] S6. The coating slurry is applied to both sides of the polyolefin base film and dried to obtain a composite film;
[0072] S7. Dissolve 70 g of ammonium borate in 1000 g of water to obtain an impregnated material;
[0073] S8. The composite membrane is immersed in 20 g of the impregnating material for 20 minutes, and after drying, a composite ceramic diaphragm having both heat resistance and liquid retention is obtained.
[0074] Comparative Example 1:
[0075] Compared with Example 1, this comparative example does not add a boron-containing reinforcing agent during the preparation of the composite ceramic diaphragm that takes into account both heat resistance and liquid retention. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a ceramic diaphragm is obtained.
[0076] Comparative Example 2:
[0077] Compared with Example 1, this comparative example only replaces "boric acid-coated carbon nanotubes" with "carbon nanotubes", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a ceramic diaphragm is obtained.
[0078] Comparative Example 3:
[0079] Compared with Example 1, this comparative example only replaces the "boric acid-coated carbon nanotubes" with "borate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a ceramic diaphragm is obtained.
[0080] Comparative Example 4:
[0081] Compared with Example 1, this comparative example does not add impregnation liquid during the preparation process of the composite ceramic diaphragm that takes into account both heat resistance and liquid retention. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a ceramic diaphragm is obtained.
[0082] Comparative Example 5:
[0083] The difference between this comparative example and Example 1 is that in this comparative example, the impregnation liquid and the coating slurry are mixed evenly and then coated on the surface of the ceramic coated diaphragm. The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, a ceramic diaphragm is obtained.
[0084] Performance Testing
[0085] Referring to GB / T6672-2001 "Mechanical measurement method for the determination of thickness of plastic films and sheets", the thickness of each group of samples in Examples 1-4 and Comparative Examples 1-5 was measured using a THI-1801 thickness gauge in μm;
[0086] Referring to GB / T135I9-2016 standard, the thermal shrinkage rate (%) of each group of samples in Examples 1-4 and Comparative Examples 1-5 placed in an environment of 150° C. for 1 hour was measured using a FST-3102 film thermal shrinkage performance tester;
[0087] Referring to ISO15105-1:2007 "Plastics-Film and Sheeting Part 1: Diferential pressure Methods" standard, the air permeability value s / 100ml of each group of samples in Examples 1-4 and Comparative Examples 1-5 was measured using a GTR-704R air permeability meter;
[0088] Referring to QB / T2303.11-2008 "Battery pulp layer paper Part 11: Determination of liquid absorption rate", the liquid absorption rate (%) and liquid retention capacity (%) of each group of samples in Examples 1-4 and Comparative Examples 1-5 were measured by weighing method, and each group of samples to be tested was immersed in the electrolyte for 120 minutes to obtain the liquid absorption rate. The calculation formula of the liquid absorption rate is as follows:
[0089] ε(%)=[(M1-M0)] / M0×100%
[0090] Where ε is the liquid absorption rate (%); M0 is the mass of the dry film (g); M1 is the mass of the wet film (g);
[0091] Referring to GB / T30447-2013 standard, the contact angle of each group of samples in Examples 1-4 and Comparative Examples 1-5 to the electrolyte was measured using a JC2000D1 contact angle tester;
[0092] The adhesion of the ceramic diaphragms prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was tested using a plastic sealing roller press and a universal tensile tester, wherein the roller pressing temperature was set to 113°C, and the two ceramic diaphragms were folded in half and aligned at the edges, sandwiched between two PET films, and the temperature of the hot roller was tested with a temperature gun. After reaching the set temperature, the roller press switch was turned on, and the films were placed in parallel in the plastic sealing machine. After all the films left the plastic sealing machine, the PET film was peeled off, and the adhesion between the ceramic diaphragms was tested using a universal tensile tester peeling method. The results are shown in Table 1 below:
[0093] Table 1
[0094]
[0095] Data Analysis:
[0096] It can be seen from Table 1 that the ceramic diaphragms prepared in Examples 1 to 4 have lower thermal shrinkage, higher air permeability, higher liquid absorption rate, higher liquid retention capacity, smaller contact angle and greater adhesion.
[0097] However, in Comparative Example 1, no boron-containing reinforcing agent was added, in Comparative Example 2, the carbon nanotubes were not coated with boric acid, in Comparative Example 3, the "boric acid-coated carbon nanotubes" were replaced with "borates", in Comparative Example 4, no impregnation liquid was added, and in Comparative Example 5, the impregnation liquid and coating slurry were mixed evenly and then coated on the surface of the ceramic coated diaphragm. The overall performance of the ceramic diaphragms finally obtained was poor.
[0098] This is because the boron-containing enhancer provided by the present invention is a boric acid-coated carbon nanotube, which itself has a large cavity and can increase the liquid retention capacity of the ceramic diaphragm. At the same time, the compounding of the boric acid coated on the outer layer and the impregnation solution can increase the cross-linking degree inside the system, thereby increasing the temperature resistance of the ceramic diaphragm. In addition, the introduction of the impregnation solution increases the affinity of the ceramic diaphragm for the electrolyte, thereby achieving the goal that the ceramic diaphragm has both temperature resistance and a high liquid absorption rate and liquid retention capacity.
[0099] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A composite ceramic diaphragm having both heat resistance and liquid retention, characterized in that: The diaphragm includes a ceramic coated diaphragm and a modified coating coated on at least one surface thereof; The modified coating is obtained by coating the coating slurry on the surface of the ceramic coating diaphragm, drying it and then soaking it in an impregnation liquid; The mass ratio of the coating slurry to the impregnating material is 100:10-20; The coating slurry comprises the following raw materials by weight: 0.1-0.3 parts of alkaline metal compound, 3-5 parts of binder, 40-80 parts of hydroxyl-containing polymer, 20-50 parts of boron-containing reinforcing agent, 0.5-1.5 parts of auxiliary agent, and 80-100 parts of deionized water; The hydroxyl-containing polymer is any one of nano bamboo charcoal powder, polyvinyl alcohol and polyethylene glycol; The boron-containing reinforcing agent is a carbon nanotube coated with boric acid; The impregnating material is an aqueous solution containing borate ions.
2. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 1, characterized in that: The preparation method of the boron-containing enhancer is as follows: S11. The carbon nanotubes were added to concentrated sulfuric acid, stirred for 10-12 hours, sodium nitrate and potassium permanganate were added, and heated in an oil bath at 38-42°C for 25-32 minutes, and then deionized water and a 30% by mass fraction of hydrogen peroxide aqueous solution were added, stirred for 20-30 minutes, and then washed and freeze-dried to obtain modified carbon nanotubes; S12. Ultrasonic disperse the modified carbon nanotubes in deionized water for 1.5-2h, add an anhydrous ethanol solution of boric acid, add the dispersed modified carbon nanotube aqueous solution dropwise into the anhydrous ethanol solution of boric acid, stir in a water bath at 60-65°C until dry, and then dry at 65-70°C for 4-5h to obtain a boron-containing enhancer.
3. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 2, characterized in that: In step S1, the usage ratio of the carbon nanotubes, concentrated sulfuric acid, sodium nitrate, potassium permanganate, deionized water and 30% hydrogen peroxide aqueous solution is 8-12 g: 20-25 mL: 0.3-0.4 g: 0.8-1.2 g: 35-40 mL: 8-12 mL.
4. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 2, characterized in that: In step S2, the mass ratio of the modified carbon nanotubes, deionized water and anhydrous ethanol solution of boric acid is 3-7:18-22:50-60, and the mass fraction of the anhydrous ethanol solution of boric acid is 8%-12%.
5. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 1, characterized in that: The alkaline metal compound is any one of nano-aluminum oxide, aluminum hydroxide and magnesium hydroxide.
6. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 1, characterized in that: The binder is any one of styrene-butadiene rubber, polyvinyl alcohol and polyvinylidene fluoride.
7. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 1, characterized in that: The auxiliary agent is any one of succinic acid, fluoroalkyl methoxy ether alcohol, sodium polyacrylate, acetylene glycol vinyl ether, fatty acid polyoxyethylene ether and polyether modified siloxane.
8. The composite ceramic diaphragm having both heat resistance and liquid retention according to claim 1, characterized in that: The concentration of the aqueous solution containing borate ions is 3%-7%; The aqueous solution containing borate ions is obtained by dissolving a boron-containing inorganic compound in water; The boron-containing inorganic compound is any one of borax, potassium tetraborate, lithium tetraborate and ammonium borate.
9. A method for preparing a composite ceramic diaphragm having both heat resistance and liquid retention according to any one of claims 1 to 8, characterized in that: The following steps are involved: S21. The binder, the hydroxyl-containing polymer and deionized water were mixed and stirred for 30-60 min to obtain a mixture A; S22. Add the alkaline metal compound, the boron-containing enhancer and the additive to the mixture A and stir for 30-60 min to obtain a mixture B; S23. The mixture B was passed through a magnetic filtration device, stirred for 5-20 min, and then filtered through a 250-mesh filter to obtain a coating slurry; S24. The coating slurry is applied to one or both sides of the polyolefin base film, and a composite film is obtained after drying; S25. Immerse the composite membrane in the impregnating material for 10-20 minutes, and after drying, obtain a composite ceramic diaphragm having both heat resistance and liquid retention.
10. An application of the composite ceramic diaphragm having both heat resistance and liquid retention according to any one of claims 1 to 8, characterized in that: For lithium-ion batteries.
Citation Information
Patent Citations
A ceramic-coated diaphragm, its preparation method, and its application.
CN108305972B
Battery diaphragm coating liquid and preparation method thereof, battery diaphragm and battery
CN113964450A
Composite separator with multilayered structure and preparation method of separator
CN104362277A
Ceramic microsphere, diaphragm containing ceramic microsphere and lithium ion battery containing diaphragm
CN112531290A
Boron-containing modified diaphragm, preparation method and application thereof, and battery containing diaphragm
CN112928387A